Biogeography-based optimisation for road recovery problem considering value of delay after urban waterlog disaster. (2017) - Meng, Lingpeng; Kang, Qi; Han, Chuanfeng; Hu, Shaolong
An urban waterlog disaster (UWD) is caused by a rainfall when the urban drainage system fails to drain off the water produced by the rainfall. To reduce the influence of the waterlog disaster on society, a road recovery planning approach is developed that performs water volume estimation, and pumps collection, assignment, and transportation after a waterlog disaster. A mixed-integer programming model that considers value of delay to travellers was formulated. A biogeography-based optimisation (BBO) algorithm was presented to solve the problem. A real-world example of waterlog (caused by torrential rain on August 12, 2011, in the Pudong district of Shanghai, China) was presented using numerical analysis. The proposed approach emerges as a decision-making tool to help decision makers evaluate diverse recovery strategies before an UWD occurs, with the aim of optimising trade-off between economic costs and value of delay.